EFFECT OF LIME AND FERTILIZERS APPLIED AT VARIABLE RATE ON THE SOIL CHEMICAL ATTRIBUTES AND PRODUCTION COSTS OF A TANZANIA GRASS PASTURE INTENSIVE MANAGED - Bernardi, A. C. de C.; Bueno, J. O. de A.; Laurenti, N.; Santos, K. E. L.; Alves, T. C. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Knowledge on spatial variability of soil properties is useful for the rational use of inputs, as in the site-specific application of lime and fertilizer. Intensive pasture management integrates different technologies such as soil liming and fertilization, irrigation and rotational grazing. Since the lime and fertilizer are key factors for the intensification of pasture systems, precision agriculture (PA) is the tool to improve the efficiency of use of these issues. The objective of this research was to map and evaluate the spatial variability of soil properties after liming and phosphate fertilizer applying at variable rate and production costs of an intensively managed pasture. The field study was carried out in a 1.7-ha area of Tanzania grass pasture in São Carlos, SP, Brazil. In the following season, after soil correction with limestone and fertilization with phosphorus and potassium using variable rate technology, soil samples were collected at 0-0.2 m depth, and each sample represented a paddock. The spatial variability of soil properties and site-specific liming and fertilizer needs were modeled using semi-variograms and data interpolation was done. The results showed that the variable rate technology (VRT) of limestone and simple superphosphate provided increases in pH, P, Ca, Mg and V% values. The VRT of inputs can be used as a tool for correction and fertilization of the soil leading to greater homogeneity of soil chemical attributes, and also reducing the production cost.